Improvement product design quality to reduce warranty cost in aftermarket sales for OEM’s customer - Abdul Hamid, Nor Hissham; Ismail, Mohd Fauzi; Khalit, Muhammad Ilham; Abdul Wahab, Abdul Malek; Adull Manan, Nor Fazli (UiTM Press, 2025)
Improving product quality and reducing warranty costs are critical objectives for Original Equipment Manufacturers (OEMs) and their aftermarket sales operations. For automotive component suppliers, analysing warranty claims is a standard practice to identify and mitigate product defects. Effective warranty cost management demands robust internal processes, innovative product designs, and early defect detection mechanisms. This study addresses the critical role of warranty claim analysis in mitigating warranty costs for automotive component suppliers, particularly in OEM aftermarket sales. Accurate warranty data analysis is pivotal for identifying defect root causes and implementing effective corrective actions. However, challenges such as incomplete data, like missing vehicle delivery dates, introduce uncertainty in forecasting and reliability assessments. This research proposes a systematic methodology to enhance vehicle warranty data analysis, focusing on reliability and robustness improvements to reduce warranty costs. The methodology consists of three phases. Phase 1 involves collecting and analysing warranty claims data from two batches: historical claims (2016–2020) and new claims (2021). Phase 2 investigates root causes using Original Failure Part (OFP) data and conducts diagnostic studies through in-person or remote assessments. Phase 3 introduces a component repair strategy aimed at reducing warranty claims by ensuring accurate fixes and improved service parts management. Results demonstrate the effectiveness of this approach, particularly in alternator component repairs, achieving a significant cost saving of RM 68,000 and a 73% reduction in warranty claims. These findings underscore the potential for enhanced profitability, strengthened customer trust in products and services, and minimized downtime for end-users. This research offers a practical framework for improving quality management and operational efficiency, contributing to sustainable growth in the automotive industry.